Granular shocks to corporate leverage and the macroeconomic transmission of monetary policy - Fédéric Holm-Hadulla; Claire Thürwächter (European Central Bank (ECB), 2024)
We study how shocks to corporate leverage alter the macroeconomic transmission of monetary policy. We identify leverage shocks as idiosyncratic firm-level disturbances that are aggregated up to a size-weighted country-level average to generate a Granular Instrumental Variable (Gabaix and Koijen, forthcoming). Interacting this instrumental variable with high-frequency identified monetary policy shocks, we find that transmission to the price level strengthens in the presence of leverage shocks, while the real effects of monetary policy are unaffected. We show that this disconnect can be rationalized with an internal devaluation channel. Economies experiencing an increase in leverage exhibit a stronger monetary policy-induced contraction in domestic demand. This, however, is counteracted by a weaker contraction in exports, facilitated by their improved price competitiveness.
Keywords: C36; E22; E52; 330; Monetary policy transmission; Corporate leverage; Granular Instrumental Variable; Micro-to-macro analysis